2010
DOI: 10.1080/07399331003759274
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Unintended Pregnancy and HIV/STIs Among Latinos in Rural Communities: Perspectives of Health Care Providers

Abstract: Latino women in the United States are disproportionately at risk for unintended pregnancy, HIV, and sexually transmitted infections (STIs). We conducted nine focus groups with health care practitioners who provide reproductive health care to Latinos in rural areas of the Northwest. From the practitioner perspective, we explored barriers and facilitators to the acquisition and use of contraceptives and to the prevention of HIV/STIs among rural Latinos. Suggestions for improving reproductive health care included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…People living in rural and remote areas also may be disadvantaged by limited access to sources of health information [11]; thus, rural adolescents may not be aware of family planning service providers located near them. Lack of transportation and excessive distances to clinics pose additional barriers to accessing family planning services for rural youth [12,13]. Concerns about confidentiality and privacy also can be exacerbated in rural communities.…”
Section: Implications and Contributionmentioning
confidence: 99%
“…People living in rural and remote areas also may be disadvantaged by limited access to sources of health information [11]; thus, rural adolescents may not be aware of family planning service providers located near them. Lack of transportation and excessive distances to clinics pose additional barriers to accessing family planning services for rural youth [12,13]. Concerns about confidentiality and privacy also can be exacerbated in rural communities.…”
Section: Implications and Contributionmentioning
confidence: 99%
“…Previous studies have shown that minority women have lower levels of knowledge and more misconceptions about birth control compared to white women. 31 , 32 Similarly, adolescents also have limited knowledge about contraception, as evidenced by one study in which only 14.7% of women aged 14 to 24 years reported knowledge of LARC methods. 33 Among Latinas, perceived side effects, including fears about cancer, infertility, and lower sex drive, resulted in women not choosing certain methods of birth control.…”
Section: Barriers To Contraceptionmentioning
confidence: 99%
“… 33 Among Latinas, perceived side effects, including fears about cancer, infertility, and lower sex drive, resulted in women not choosing certain methods of birth control. 31 …”
Section: Barriers To Contraceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The men in this study offered many of their own ideas about how to best disseminate information about reproductive health and SRHS, such as airing public service announcements on Latino radio or television stations, placing articles about reproductive health or ads for services in Latino newspapers, or distributing pamphlets in locations where Latinos frequent, such as Laundromats or Latino stores. Men also emphasized the importance of providing information in Spanish, a proposition that has received support from numerous other studies (Becker et al, 2009;Branch, Harvey, Zukoski, & Warren, 2010;Britigan et al, 2009;Hunter, Fernandez, Lacy-Martinez, Dunne-Sosa, & Coe, 2007). Britigan et al (2009) also suggest that language problems can be circumvented by turning to computers and the use of the Internet as a way to access health information in a user's native language.…”
Section: Discussionmentioning
confidence: 99%